Post-Colonialism in Theory and Practice (KULT_online, 2010)
Volume seven in the series WVT Handbooks on Literary Studies, Post-Colonial Theory and Literatures combines a panoramic view of major theoretical trajectories with in-depth analyses of a considerable number of novels, poems and plays. The product of the joint labor of three authors, the book is remarkably rich in its handling of abstract concepts in Part I, and broadly thought-provoking in its treatment of works of literature in Part II. Despite very few inconsistencies in their explorations, the authors have produced a handbook that, in the last analysis, is instructive, informative and insightful.